Exploratory study of pattern mining for information extraction tasks. - Wong, Chin Khuen. (2008)
Developing machine learning techniques that can recognize and understand natural language text have been a long-standing problem. Researchers in Information Extraction have shifted their focus to shallow text processing involving pattern matching from full-fledged natural language processing and text comprehension. The rapid growth of the World Wide Web has helped to boost the interest in developing Web-based information extraction using Wrapper.